The Implication of Opportunistic Behavior Towards a Financial Report Conservatism : A Study of Banking Company Go-Public at BEI - Novi Darmayanti; Nur Suci Mei (International Conference On Law, Business and Governance (ICon-LBG), 2013)
Backgraund of study Opportunistic behavior is a conflict of interest between investors and creditors due to the tendency of investors in undergoing a wealth transfer from creditors (Fama, 1978a; 1978b). Kreditors urges a rather high interest rates and the implementation of a more conservative financial report method (Jong and Dijk, 1999). The concept of opportunistic behavior is divided into three: (1) in terms of direct transfer of wealth, the dividend payments is too high and fund sources from the debt tends to become a major priority (Smith and Warner (1979); (2) In the case of asset substitution, in which a company is involved in the high-risk projects (Jensen and Meckling (1976); (3) in the case of underinvestment, in which investment prospect and growth will not be implemented by investors unless there is a loan from the creditors. These three concepts leads to the wealth transfer from creditors to investors. In short, investors prefer funding obtained from debt. In other words, the higher the debt of a company, the more potential opportunistic behavior between investors and creditors (Fama dan Miller, 1972). Those three concepts become main factors of financial report conservatism. The trickery cases in Indonesia ultimately indicate the low level of conservatism implemented by a company in order to make their financial report (Ahmed et.al, 2002). Therefore, it becomes a motivation in this study and only a few studies were conducted, particularly in Indonesia (Ahmed et. al, 2002). The problem of the study. According to the background stated before, the problem of this study is whether opportunistic behavior influences financial report conservatism. Opportunistic behavior conducted in this study is associated with the rate of operation uncertainty, the rate of dividend payments and the debt rate. The aim of the study (1) To examine the accounting conservatism from its upside parts, especially on its relation with debt contract and dividend payments; (2) To examine the phenomenon of debt contract and dividend payments that potentially generates opportunistic behavior regarding the dividend policy. Related Studies. Qiang (2003) stated that investors are able to transfer their wealth from creditors using a high dividend payments, a new debt funding, and transfer, acquisition or assets removal. In order to manage this conflict, the restrictions of dividends, capital structure and assets conversions. In order to deal with the problem, the pembatasan dividen, capital structure, and change of aktiva. Hirshleifer and Thakor (1992) stated that the pembatasan is usually included in perjanjian debt. Therefore, creditors tend to prefer a conservative financial report. Manager urges to minimize the debt cost of company. A company can lower its debt cost by considering a more restricted limitation rules regarding divident payments and must implement the conservative accounting. In the studies conducted by Qiang (2003) and Hirshleifer & Thakor (1992), there were not any discussions about the implication of opportunistic behavior towards financial report conservatism. Hence, it is essential to have a further study regarding this problem. Methods of the Study Quantitative method. Secondary data. An analysis unit is a perusahaan perbankan that go-public at BEI during 2011-2012. The hypothesis of the study is that there is an implication between opportunistic behavior and financial report conservatism. The hypothetical examination was conducted by applying logistic regression, while the tools of analysis implemented SPSS.The Implication for Business Practices / Practical Contribution (1) A manager is able to consider the decision-making, particularly related with opportunistic behavior, towards financial report conservatism, (2) An accountant tends to be more conservative in making and presenting the financial report based on SAK. Theoretical Contribution this study contributes to Market Based Accounting Research.